Palliative Care Consultations in Nursing Homes and Reductions in Acute Care Use and Potentially Burdensome End‐of‐Life Transitions. Issue 11 (19th September 2016) - Miller, Susan C.; Lima, Julie C.; Intrator, Orna; Martin, Edward; Bull, Janet; Hanson, Laura C.
Abstract : Objectives: To evaluate how receipt and timing of nursing home (NH) palliative care consultations (primarily by nurse practitioners with palliative care expertise) are associated with end‐of‐life care transitions and acute care use Design: Propensity score–matched retrospective cohort study. Setting: Forty‐six NHs in two states. Participants: Nursing home residents who died from 2006 to 2010 stratified according to days between initial consultation and death (≤7, 8–30, 31–60, 61–180). Propensity score matching identified three controls (n = 1, 174) according to strata for each consultation recipient (n = 477). Measurements: Outcomes were hospitalizations in the last 7, 30, and 60 days of life; emergency department (ED) visits in the last 30 and 60 days; and any potentially burdensome care transition, defined as hospitalization or hospice admission within 3 days of death or two or more hospitalizations or ED visits within 30 days. Weighted multivariate logistic regression analyses were used to evaluate outcomes. Results: Residents with consultations had lower rates of hospitalization than controls, with rates lowest when initial consultations were furthest from death. For instance, in residents with initial consultations 8 to 30 days before death, the adjusted hospitalization rate in the last 7 days of life was 11.1% (95% confidence interval (CI) = 9.8–12.4%), vs 22.0% (95% CI = 20.6–23.4%) in controls, although in those with initial consultations 61 to 180 days before death, rates were 6.9% (95% CI = 5.5–8.4%), vs 22.9% (95% CI = 20.5–25.4%). Potentially burdensome transition rates were lower when consultations were 61 to 180 days before death (16.2%, 95% CI = 13.7–18.6%), vs 28.2% (95% CI = 25.8–30.6%) for controls. Conclusion: Palliative care consultations improve end‐of‐life NH care by reducing acute care use and potentially burdensome care transitions.